Melting of andesite in a microwave oven - Znamenácková I.; Lovás M.; Hájek M.; Jakabský Š. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The positive influence of the microwave radiation on the melting of rocks is described. Local melting-down of specimens and subsequent flowing-out of red-hot magmatic mass was observed when andesite samples from the location of Ruskov (Slovakia) were heated in a microwave own with an output of 900 W. After 30 min of microwave heating of an andesite specimen of defined dimensions, its complete melting was observed and the temperature measured reached the range of 1260-1280°C.